Effect of water immersion restraint stress on gastric mucosa in rats with removed salivary glands - Xu, Bo (Int J Clin Exp Pathol, 2020)
Objective: To explore the effect of salivary gland removal on water immersion restraint stress (WIRS)-induced gastric mucosal injury (GMI) in rats. Methods: Eighty male WISTAR rats were allocated into sham operation (sham) group, sham + WIRS group, salivary gland removal group, and salivary gland removal + WIRS group, with 20 rats in each group. In the sham group, skin and subcutaneous tissues were cut to expose glands. The rats in other three groups were subjected to a total salivary gland resection, and all their submandibular glands and sublingual glands and part of the parotid glands were removed, and the parotid duct was ligated. Afterwards, rats were exposed to WIRS for one and a half months and sacrificed. The severity of GMI was scored, and any histologic and ultrastructural changes were monitored. Results: There were differences in the Guth index (GMI evaluation) scores among the four groups (P=0.000), which were higher in salivary gland removal + WIRS group than those in the other three groups (all P<0.001), and were higher in the sham + WIRS group and salivary gland removal group than those in the sham group (all P=0.000). Compared with other groups, the gastric mucosa was severely injured in the salivary gland removal + WIRS group, with obvious congestion, edema, inflammatory cell infiltrate, mucosal shedding, bleeding ulcers, enlarged intercellular spaces, and damaged organelles. Conclusion: Salivary gland removal aggravates WIRS-induced GMI to a certain extent.